Assessment of an old reinforced concrete open-spandrel arch railway bridge. (October 2022) - Ozakgul, Kadir; Yilmaz, Mehmet Fatih; Caglayan, Barlas Ozden
Abstract: This paper presents assessment of a 94 years old reinforced concrete (RC) open-spandrel arch bridge with a total length of 285 m having seven major spans of 35 m, a height of 34 m and a vertical slope of 15 ‰. As the bridge was currently subjected to heavy trains having higher axle loads than it was originally designed, assessment of its actual structural condition was necessary. To determine actual in-situ behavior of the bridge, dynamic tests including a series of acceleration measurements along the bridge spans were performed. Then, 3D finite element model of the bridge was generated by using a structural analysis software based on its original constructional drawings. The initial FE model was updated using Response Surface Method (RSM) technique based on the results obtained from measurement data. The updated FE model was used for structural assessment and evaluation of the bridge under UIC-71 live loading. Rating factor and reliability index for each bridge member based on Load and Resistance Factor Rating (LRFR) approach were obtained. Results of the rating and reliability analysis showed that the most critical member of the bridge was the deck, thus strengthening and retrofitting of these deck members might be needed for live loads greater than those induced by UIC-71 train.